Web Service Discovery with additional Semantics and Clustering - Nayak, Richi; Lee, Bryan (Proceedings of the IEEE/WIC/ACM International Conference on Web Intelligence, 2007)
Due to the lack of semantic descriptions of the Web services, the search results returned by the service registries are effectively inadequate. This paper presents the Semantic Web services Clustering (SWSC) method that extends the semantic representation of services and groups the similar Web services in order to improve the service discovery. The empirical analysis shows the improvement in service discovery with the use of SWSC.